ANALISIS SIKAP PETANI TERHADAP PENGGUNAAN BENIH LADA PUTIH DI PROVINSI KEPULAUAN BANGKA BELITUNG - Trimawan, Cipta Yan; Nurmalina, Rita; Burhanuddin, . (Departemen Sosial Ekonomi Faperta Unpad, 2017)
Bangka Belitung Islands Province, known as a producer of white pepper in the international market with the name of muntok white pepper. One of the efforts to increase productivity is through the use of white pepper seeds. The most used seeds by farmers are varieties Petaling 1, LDK and Merapen. The farmersâ attitude to the selection of white pepper seeds is very important to know because they are the main agribusiness actors that will produce white pepper. The objectives of this research is to analyze the farmersâ attitude on the attributes of white pepper seeds. This research was involved 60 respondents of white pepper farmers. The analysis using fishbein multiattributes showed that the attitude of respondents prefer white pepper seed varieties Petaling 1 compared to Merapen and LDK varieties. Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Keywords: Bangka Belitung Islands Province, Fishbein Multiatribut and White Pepper Seeds